Les bûcherons-tâcherons, des travailleurs restés à l’écart du salariat - Julien Gros (La Nouvelle Revue du Travail)
Contract lumberjacks have more features in common today with independent workers than with wage earners. Employed under short-term contracts, paid on a piece-rate basis and owners of their work tools, theirs is a profession that has long deviated from the general trend towards wage-earning, attesting to the diversity of employment systems even as the wage system has become the dominant social modus operandi. Yet despite lumberjacks’ economically dominated position, they still benefit from a great deal of autonomy in terms of their work organisation, applying a kind of accounting that is very different from usual employment contracts. The present article addresses the social and historical conditions defining the boundaries between independent work and wage-earning in socially dominated activities.